Alaska Native Patient and Provider Perspectives on the Multitarget Stool DNA Test Compared With Colonoscopy for Colorectal Cancer Screening - Diana G. Redwood; Ian D. Blake; Ellen M. Provost; John B. Kisiel; Frank D. Sacco; David A. Ahlquist (SAGE Publishing, 2019)
Objective: Alaska Native (AN) people have among the world's highest rate of colorectal cancer (CRC). We assessed perceptions of AN people and their health care providers of a new take-home multitarget stool DNA test (MT-sDNA; Cologuard) relative to colonoscopy. Methods: Cross-sectional surveys of AN people aged 40 to 75 years (mailed) and providers (online). Results: Participants included 1616 AN patients (19% response rate) and 87 providers (26% response rate; 57% AN people). Over half (58%) of patients preferred colonoscopy for CRC screening, while 36% preferred MT-sDNA. Unscreened patients were significantly more likely to state a preference for MT-sDNA than previously screened patients (42% vs 31%, P < .05) as were younger patients (<60 years old) compared with older patients (40% vs 30%, P < .05). Most providers thought that MT-sDNA would improve screening rates (69%), would recommend if available (79%), and be implementable (79%). Perceived barriers differed substantially between patients and providers in both type and magnitude. Leading colonoscopy barriers reported by patients were travel (44%) and bowel preparation (40%), while providers thought that fear of pain (92%) and invasiveness of the test (87%) were the primary barriers. For MT-sDNA, patients' belief that colonoscopy was better (56%) and not knowing how to do the test (40%) were primary barriers, while providers thought stool collection (67%) and having a stool sample in their home (63%) were leading barriers. Conclusions: This study found that MT-sDNA has potential acceptability among AN people and their health care providers. Both groups reported a willingness to use MT-sDNA and did not perceive major barriers to its use. This preference was especially true of unscreened and younger patients. The majority of providers indicated they would use MT-sDNA if available and that it would improve CRC screening rates. In this population, where colonoscopy access is limited, MT-sDNA has the potential to improve CRC screening adherence.